PENYULUHAN HUKUM DAN SEKS UNTUK REMAJA - Alfrid Sentosa; Betty Karya; Fauzi Rahman; Dewi Ratna Juwita; Manya Manya; Kilat Kasanang (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The purpose of this service is to provide a clear and comprehensive understanding of the law related to sexuality, as well as to raise awareness among adolescents about the importance of making wise and responsible decisions. The methods used in this service are a) lectures, b) discussions, c) pre-test and post-test questions. The result obtained from this service activity is an increase in understanding of students, which is 15-20 percent of the total sample of counseling participants